A COMPARATIVE STUDY OF POLYPHENOLIC CONTENT IN ACACIA CATECHU BARK EXTRACTS AND BIBLIOGRAPHIC ANALYSIS WITH REFERENCE TO GUNA (MADHYA PRADESH), INDIA - Archana Tiwari; Avinash Tiwari (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Plant-based polyphenolic compounds are important phytonutrients found in many meals such as fruits, vegetables, tea, coffee, and red wine. The literature study has gathered enough evidence confirming the existence of the same substance in the bark of Acacia catechu plants. The literature review verified that the dense forest with comparable plant life in Guna district of Central India has not been systematically studied. This research aims to analyze the total polyphenolic content of A. catechu bark from this location. Methods: Thirty samples of test plants were collected from the research area in different seasons for this investigation. Each sample was made using six distinct solvents. Subsequently, quantitative testing was conducted using a standardized laboratory approach. Bibliographic analysis was conducted to confirm and establish a connection between the current study and previous research. Results: The results indicated that the test parameter was present in large quantities in all polar extraction systems, but only insignificant amounts were seen in chloroform and benzene. The comparative bibliographic investigation was confirmed the advantageous uses of the same. Conclusion: This exploratory investigation potentially identified novel, cost-effective, and easily accessible sources of polyphenolic chemicals from the local flora of Guna region and serve as the foundation for future researches on the same.